2018
DOI: 10.1016/j.marpetgeo.2017.11.030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of in situ stress and fault reactivation on seal integrity in the East Irish Sea Basin, UK

Abstract: Despite having been affected by several stages of exhumation during the Cretaceous and Cenozoic, the contemporary stress state of the East Irish Sea (EISB) is poorly characterised. As the basin is mature in terms of exploitation of hydrocarbons, future exploration beyond the conventional Sherwood Sandstone Group reservoir (Triassic) necessitates a greater understanding of the in situ stress field, while proposed natural gas storage and carbon sequestration schemes also require detailed stress field information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 72 publications
(108 reference statements)
0
25
0
Order By: Relevance
“…Since the capillary pressure-controlled properties are associated with the pore size distribution and wettability, the lithology and mineral composition of the mudrock at the reservoir/seal interface becomes important when estimating the capillary sealing efficiency of the caprock overlying potential CO2 storage sites. The MMG, which overlies potential CO2 storage formations such as the Sherwood Sandstone Group and its North Sea equivalent, the Bunter Sandstone Formation (Noy et al, 2012;Williams et al, 2018), equally serves as a good example here. At the reservoir/seal interface, transitional lithologies commonly exist between the Sherwood Sandstone and the Mercia Mudstone (Newell and Shariatipour, 2016;Seedhouse and Racey, 1997;Shariatipour et al, 2016b).…”
Section: 3mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the capillary pressure-controlled properties are associated with the pore size distribution and wettability, the lithology and mineral composition of the mudrock at the reservoir/seal interface becomes important when estimating the capillary sealing efficiency of the caprock overlying potential CO2 storage sites. The MMG, which overlies potential CO2 storage formations such as the Sherwood Sandstone Group and its North Sea equivalent, the Bunter Sandstone Formation (Noy et al, 2012;Williams et al, 2018), equally serves as a good example here. At the reservoir/seal interface, transitional lithologies commonly exist between the Sherwood Sandstone and the Mercia Mudstone (Newell and Shariatipour, 2016;Seedhouse and Racey, 1997;Shariatipour et al, 2016b).…”
Section: 3mentioning
confidence: 99%
“…The allowable bottom-hole-pressure (BHP) is set to 75% of a lithostatic pressure gradient assumed to be 22.5 MPa/km (after Noy et al, 2012). This is ~90% of the minimum horizontal stress magnitude in the East Irish Sea Basin as estimated by Williams et al (2018). In order to accurately approximate the magnitude of expected fluid pressure increase resulting from CO2 injection, cells towards the top of the reservoir and at the base of the caprock are thinner.…”
mentioning
confidence: 99%
“…The orientation of the UK and UKCS stress field has been studied extensively (Williams et al, 2015(Williams et al, , 2018Holford et al, 2016;Kingdon et al, 2016;Fellgett et al, 2017b)). Kingdon et al (2016) reported that the orientation of S HMax across the UK landmass is 150.9°± 13.1°, which is the result of ridge-push forces associated with the Mid Atlantic Ridge (Klein and Barr, 1986;Gölke and Coblentz, 1996).…”
Section: Orientation Of the Uk Stress Fieldmentioning
confidence: 99%
“…The latest edition of the World Stress Map (WSM) includes all of the current openly available stress data for the UK (Heidbach et al, 2016) which has been greatly expanded by recent studies (Williams et al, 2015(Williams et al, , 2018Holford et al, 2016;Kingdon et al, 2016). Information from the WSM has previously been used to estimate stress magnitudes .…”
Section: Introductionmentioning
confidence: 99%
“…The characterisation of fault properties in caprock strata is of particular relevance, as these structures may have a strong impact on the likely integrity of fluid traps, potentially allowing the development of fluid flow bypass systems through the seal units (Cartwright et al, 2007;IEAGHG, 2017b;Maia et al, 2016;Petrie et al, 2014). At a regional scale, the location of faults can be interpreted on 3D seismic data, allowing broad scale mapping of networks and other fluid-flow features (Backe et al, 2015;Streit et al, 2005;Williams et al, 2018). Reliably constraining other properties such as in situ stress relies upon a high density of subsurface data obtained from boreholes (Sibson, 1995;Williams et al, 2018).…”
Section: Introductionmentioning
confidence: 99%